PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PENGELOLAAN KEUANGAN DAERAH KABUPATEN SIDENRENG RAPPANG - Gazali Amin; Busrin Raihana Mas'ud (PIRSAP (Paser Institute for Scientific Research and Publications), 2024)
This research aims to test and analyze the influence of competency on employee performance at the Regional Financial Management Agency office of Sidenreng Rappang Regency. The population in this study was the State Civil Apparatus (ASN) at the Regional Financial Management Agency office of Sidenreng Rappang Regency, totaling 70 ASN. The sampling method used was random sampling and the sampling technique was using the Slovin formula. The data collection method is through distributing questionnaires, then the data is analyzed using multiple linear regression analysis using SPSS 24 software. Based on the partial results or t test, the competency variable shows the results of t-count (2.040) > t-table (1.996) so it can be said that overall partial competence has a significant positive effect on job satisfaction.